Pendidikan Keteladanan Shalahuddin Al-Ayyubi Konteks Pendidikan Islam Era Society 5.0 - Ngatmin Abbas; Joko Subando; Muhammad Zaki Tamami (Yayasan Azhar Amanaa Yogyakarta, 2023)
This research aims to explore the concept of exemplary education implemented by Shalahuddin Al-Ayyubi and its relevance in the context of modern Islamic education. The research methodology employed was literature review to examine sources related to the life and education of Shalahuddin Al-Ayyubi. The findings indicate that the exemplary education implemented by Shalahuddin Al-Ayyubi has a significant impact on character formation, moral leadership development, and the strengthening of religious identity among students. The implication of this research is the need for the implementation of exemplary education in the context of modern Islamic education to nurture a generation that is of high quality, ethical, and committed to Islamic values. In the complex contemporary era, an education approach based on the exemplariness of Shalahuddin Al-Ayyubi can serve as a guide in facing the social, moral, and spiritual challenges encountered by students. By understanding and adopting the principles of traditional Islamic education implemented by Shalahuddin Al-Ayyubi, modern Islamic education can enrich educational approaches to produce individuals of dignity, noble character, and commitment to Islamic teachings.